Role of information and communication technologies for improving input efficiency of horticultural crop production (Indian Journal of Arid Horticulture, 2025)
Indian farming community is passing through a phase of reducing incomes, uncertain and unpredictable markets and weather conditions. They need advance information and intelligence on agricultural commodities and their supply/demand position in the local as well as global markets. They also need advises on the impending climate/weather parameters so as to regulate their choice of crops and farm management and operations. They have to be enabled to face the global competition. For that Information and communication Technologies (ICT) are very use full. The use of ICT in agriculture in general and rural livelihood security in particular remains restricted in India. Effective utilization of ICT has the potential to make the rural communities in India prosperous. Failure to exploit the benefits of ICT would make them isolated, victims of the vicious cycle of poverty and widen the gap between rich and poor people, thereby affecting social equality and livelihood security. The use of ICT should not be restricted to simply establishing information flow channels, rather we should find a way to integrate it with the various livelihood needs (natural, social, human, physical and financial) of the rural community. The narrow ICT coverage is found to be financially non-viable. Further, no single agency can effectively deliver this critical input. Besides the public sector, the need for a proactive participation by the private sector, NGOs and other civil society organisations is being increasingly felt. For ICT initiatives to be successful and sustainable in the long run, collaborative efforts are indispensable. This digital development in rural areas of India facilitates rural prosperity, rural empowerment, and a warehousing of data for development, increasing input efficiency and productivity, reducing cost of service delivery etc. a step towards digital inclusions to foster rural enterprise in India.
Keywords: ICT; horticulture; GPS; GIS; precision farming